Response of runoff in the upper reaches of the Minjiang River to climate change. Issue 1 (12th June 2021) - Yang, Kebi; Chen, Ting; Ao, Tianqi; Zhang, Xu; Zhou, Li; Gao, Danyang
Abstract: Climate change affects the water cycle in different regions. The response of annual runoff and seasonal distribution to climate change in the upper reaches of the Minjiang River during 2021–2050 was studied by coupling the Statistical Downscaling Model (SDSM) and the Soil and Water Assessment Tool (SWAT). This model was driven by the second-generation Canadian Earth System Model (CanESM2) under RCP2.6, RCP4.5, and RCP8.5 scenarios. The results show that the runoff in the upper reaches of the Minjiang River has a unique response to climate change. The maximum and minimum temperatures will increase with the increase in emissions, especially in December–January. The daily precipitation shows an upward trend, especially in July–August in the RCP4.5 scenario. The annual runoff shows an upward trend with the increase in emissions. Compared with the current increase of 13–26%, the most prominent period is November–April. Because the study area covers high mountains and gorge landforms, the altitude difference is great, and the influence of evapotranspiration and snow melting processes is more prominent, causing the monthly runoff to decrease in June–July with an increase in precipitation. From April to May, precipitation decreased while runoff increased. HIGHLIGHTS: The first study on annual runoff, seasonal distribution, and primary tributaries of the upper Yangtze River response to climate change in the Minjiang River upper reaches. Analysis of differences among the Minjiang upper reaches and other upper reaches of the Yangtze River. Runoff variation causes about seasons and three typical concentration paths. Coupling SDSM and SWAT analyzes application.